Source records 1-6, 1968-1971 - Ashley, Robert 1930-2014; Behrman, David; Austin, Larry; Bryant, Allan; Lucier, Alvin; Woodbury, Arthur; Riener, Mark; Lunetta, Stanley; Cross, Lowell; Lora-Totino, Arrigo; Curran, Alvin; Lockwood, Annea (New York Pogus productions, 2008)
CD One - Source Records 1 and 2 Robert Ashley, The Wolfman; David Behrman, Wave Train; Larry Austin, Accidents; Allan Bryant, Pitch OutCD Two - Source Records 3 and 4 Alvin Lucier, I am sitting in a room; Arthur Woodbury, Velox; Mark Riener, Phlegethon; Larry Austin, Caritas; Stanley Lunetta, moosack machineCD Three - Source Records 5 and 6 Lowell Cross, Video II (B)/(C)/(L); Arrigo Lora-Totino, english phonemes; Alvin Curran, Magic Carpet; Annea Lockwood, Tiger BalmPogus is extremely proud to reissue the recordings included in the seminal new music journal, Source: Music of the Avant Garde, Vols. 1-6, Issues 1-11, Source Records 1-6, 1967-1973. The original six ten-inch LP Source Records contained some of the most important experimental music of the nineteen-sixties to mid nineteen-seventies and they have now been reissued as a 3 CD set. Source ended publication in 1973, having published, since 1967, contemporary musical materials, scores, articles, interviews, photo essays and recordings over seven years, with up to 2000 subscribers to the semiannual journal: the subscribers avidly anticipated receiving two new and critically acclaimed issues each year during that period.Most of the original tape masters for the records, after over forty years, have vanished or have seriously deteriorated; hence, we have carefully transferred, noise-reduced, and crackle-removed all the actual LP record tracks to the digital medium, then mastered to the compact disc format for this reissue: the result is an authentic recreation of the original LP, characteristic sound.Review Review